The Reasons for the Qur’anic Repetition in the Interpretation of Al -Ragheb Al -Isfahani - عبد الزهرة مهدي ناجي; عبد الله ظاهر أحمد (Journal of College of Education, 2022)
Verbal repetition was an expressive flaw in the interpretation of al-Ragheb al-Isfahani, in which al-Ragheb stated how a word impacts a word or a structure on a structure inside the blessed Qur’anic text. It has been discovered that the most frequently repeated words indicate emphasis, regardless of whether the repetition occurs in a single surah or throughout the Noble Qur’an. Furthermore, years of research have revealed the reasons for verbal repetition in this interpretation of nouns, verbs, and letters.